Latin American Urban Violence as a Development Concern: Towards a Framework for Violence Reduction - Caroline Moser and Cathy Mcilwaine (My University, 2016)
Despite growing recognition of urban violence being a serious development con- straint in Latin America, there is contestation concerning its categorization, underlying causes, costs and consequences, and violence-reduction solutions. This article seeks to contribute to a bet- ter understanding of the complexity of everyday violence in poor urban communities in terms of both ongoing analytical debates as well as operational solutions. Drawing on the research litera- ture, as well as recent participatory urban appraisals of violence in Colombia and Guatemala, and Central American violence-reduction guidelines, it develops a framework to explain the holistic nature of violence and to provide operationally relevant methodological tools to facilitate cross- sectoral violence-reduction interventions.